Transport layer protocols for haptic virtual environments - Dodeller, Stephane (University of Ottawa (Canada), 2004)
Collaborative Virtual Environments require the exchange of update messages between remote locations. Network impairments such as delay, delay variations and packet loss impede collaboration, especially when haptic devices are used. This thesis compares three transport-layer protocols that address this concern, and describes the framework designed to evaluate them. Two previously proposed protocols have been studied (based on key updates acknowledgment and updatable queue on the sender side, respectively), and a new protocol is proposed. This new protocol adds buffering on the receiver side. By reducing the delay variation, it significantly helps collaboration, whereas it has been shown that buffering on the sender side should be avoided. Two applications that make use of a haptic device have been designed and implemented for the tests: a tracheostomy simulation and a box carrying application.
Keywords: Engineering, Electronics and Electrical.